On the elasto-plastic stability problem of shells of revolution - Bich, Dao Huy (Vietnam Journal of Mechanics, 2003)
This paper deals with the elasto-plastic stability problems of shells of revolution subjected to complex loading process. The governing equations were derived and were solved by using the Bubnov-Galerkin method and the loading parameter method. Some examples were considered.